2019
DOI: 10.1155/2019/1805280
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Thermal Behavior of Nanoparticles of Mg(OH)2 to Be Used as Flame Retardants

Abstract: To study the effects of the precursor materials on the structure, the morphology, and the thermal stability of Mg(OH)2 particles, five samples were prepared by using the same method. The produced powder was characterized by using FTIR, XRD, SEM, and TEM, and the thermal stability was studied by using the thermogravimetric analysis. This study aims to use the advantage prepared material as a flame-retardant for the polymeric materials. The characterization of the obtained samples shows that Mg(OH)2 is formed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Furthermore, when Mg metal and alloys are in contact with water, or aqueous solutions containing various salts, Mg­(OH) 2 and/or MgO layers are formed as a barrier to protect their surfaces. , Similarly, Mg-based rechargeable batteries have been considered as a possible alternative to Li-based batteries owing to their higher energy density . To understand the stability of Mg-based alloys and Mg anodes in rechargeable batteries, the formation mechanism of Mg­(OH) 2 and MgO layers on the Mg surface has been characterized by in situ Raman, transmission electron microscopy (TEM), , high-voltage electron microscopy (HVEM), and electrochemical analyses. For example, Volovitch et al reported the formation of Mg­(OH) 2 on the MgO/Mg surface by a dissolution–precipitation mechanism; however, they also mentioned that this conclusion remains speculative . Baumann et al reported that the dissolution rates of MgO cube in basic solution to form Mg­(OH) 2 nanosheets are correlated to the particle sizes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when Mg metal and alloys are in contact with water, or aqueous solutions containing various salts, Mg­(OH) 2 and/or MgO layers are formed as a barrier to protect their surfaces. , Similarly, Mg-based rechargeable batteries have been considered as a possible alternative to Li-based batteries owing to their higher energy density . To understand the stability of Mg-based alloys and Mg anodes in rechargeable batteries, the formation mechanism of Mg­(OH) 2 and MgO layers on the Mg surface has been characterized by in situ Raman, transmission electron microscopy (TEM), , high-voltage electron microscopy (HVEM), and electrochemical analyses. For example, Volovitch et al reported the formation of Mg­(OH) 2 on the MgO/Mg surface by a dissolution–precipitation mechanism; however, they also mentioned that this conclusion remains speculative . Baumann et al reported that the dissolution rates of MgO cube in basic solution to form Mg­(OH) 2 nanosheets are correlated to the particle sizes .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Similarly, Mg-based rechargeable batteries have been considered as a possible alternative to Li-based batteries owing to their higher energy density. 17 To understand the stability of Mg-based alloys and Mg anodes in rechargeable batteries, the formation mechanism of Mg(OH) 2 and MgO layers on the Mg surface has been characterized by in situ Raman, 15 transmission electron microscopy (TEM), 18,19 highvoltage electron microscopy (HVEM), 20 and electrochemical analyses. 21−23 For example, Volovitch et al reported the formation of Mg(OH) 2 on the MgO/Mg surface by a dissolution−precipitation mechanism; however, they also mentioned that this conclusion remains speculative.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The first stage between room temperature and 200 °C can be associated with physisorption on the surface of the material, of water for the fresh material and of water, acetone, and acetonitrile for the spent material, as well as the elimination of hydroxide groups. The second stage begins at 200 °C and ends around 480 °C, corresponding to the elimination of chemisorbed species and the decomposition of Mg­(OH) 2 present in the materials to form MgO . The no significant weight loss after 480 °C shows the high stability of MgO.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh nFe 0 exhibited the two typical characteristic peaks of α-Fe 0 at 2θ of 44.8˚and 82.16˚, confirming the presence of the pure iron core. The freshly prepared Mg(OH)2 showed a mixture of crystalline and amorphous peaks, attributed to MgO (ICSD, Code: 31053), and brucite (ICSD, Code: 31053), respectively [38]. XRD pattern of fresh nFe 0 @Mg(OH)2 (100% coating ratio) showed a lower-intensity peak of α-Fe 0 , owing to the high Mg/Fe coating ratio and the moderate amorphous nature of the Mg(OH)2 coating.…”
Section: Materials Characterizationmentioning
confidence: 99%